Answer: h=7
Step-by-step explanation:
By definition the function in vertex form is:

Where (h,k) is the vertex of the parabola.
You must group the terms that contain the same variable in the function:

Complete the square as following:

Now you must rewrite it as following:

Then:
h=7
Answer:
Step-by-step explanation:
Because dividing any term by the previous term gives a constant this is a geometric sequence of the form an=y^(n-1). Since each term is four times the previous term y=4 so
an=4^(n-1)
<span>(6y3 + 17y − 3) − (4y3 − 11y + 9)
</span>= 6y3 + 17y − 3 − 4y3 + 11y - 9
= 2y3 + 28y - 12
I’m not sure but is it C?